2013
DOI: 10.1039/c3lc41359d
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-based lipid bilayer system integrated with microfluidic channels for solution exchange

Abstract: This paper proposes a solution exchange of a droplet-based lipid bilayer system, in which the inner solution of a droplet is replaced for the purpose of efficient ion channel analyses. In our previous report, we successfully recorded the channel conductance of alpha-hemolysin in a bilayer lipid membrane using a droplet contact method that can create a spontaneous lipid bilayer at the interface of contacting droplets; this method is widely used as highly efficient method for preparing planar lipid membranes. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…Alternatively, polymethilsiloxane (PDMS) is a transparent biocompatible material, which allows low-cost and simple fabrication, but its use for the formation of free-standing lipid bilayers is hindered by swelling and deformability issues in several organic solvents 13 , which are often required for artificial lipid bilayer formation 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, polymethilsiloxane (PDMS) is a transparent biocompatible material, which allows low-cost and simple fabrication, but its use for the formation of free-standing lipid bilayers is hindered by swelling and deformability issues in several organic solvents 13 , which are often required for artificial lipid bilayer formation 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this method provides a simple and efficient way of delivering compounds to ion channels, transporters, or nanopores incorporated in phospholipid bilayers. In contrast to conventional bilayer technology, the method provides a novel means of drug screening against ion channels using very small volumes of compound solutions (10-15 ll) compared to the state of the art, [19][20][21][22][23] significantly reducing the cost per screen. The chips are easy to manufacture on a wafer and could be reused if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been addressed by making smaller systems, incorporating micro-channels for solution exchange. 8,17,[19][20][21][22] For example, Stimberg et al described a flow channel, where the microfluidic channel and bilayer aperture are made separately and glued together and fluid is flown across the bilayer using a syringe pump. 19 Shao et al demonstrated a bilayer microfluidic platform that enabled rapid perfusion of liquid (>2.5 ll/min), with 100 ll samples, 21 and Le Pioufle et al demonstrated an array of wells, each with multiple small bilayers with fluidic access to both sides, where electrical recordings were performed by moving an Ag/AgCl electrode from well to well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and (G). The figure was modified from the author's previous paper 19) . s7βCD was lodged at the β-barrel of the αHL pore.…”
mentioning
confidence: 99%